THE SYSTEM OF PROOF AS THE MAIN ELEMENT OF A UNIFIED FORM OF ACTION IN PRE-TRIAL PROCEDURE REALIZATION - Ivanovich, Girko Sergey; Vladimirovich, Kharchenko Sergey; Aleksandrovich, Tsepinsky Stanislav; Yuryevich, Latyshev Sergey; Manapbaevich, Kambarov Altynbek (International Journal of Psychosocial Rehabilitation, 2020)
Subject / topic. The system of proof within the pre-trial proceedings in the matter of unified procedural form Objectives/goals. Analysis of problematic issues that have relation to the system of proof in pre-trial proceedings under the criminal procedure code of the Russian Federation. The author states that the differentiation of the form of action in pre-trial procedure predetermines that each of them has the individual system of proof, including the subject of proof, sources (procedural means) of data collection under the recognition as proof, which, as the example of an inquiry in a short form, requires appropriate changes in legislation. Methodology. Analysis, synthesis, comparison, abstraction, target setting, hypothesis formulation, concretization, monitoring. Conclusion. On the basis of legal analysis and the author’s approach to the content of the legal form of action as an institution, there is a conclusion that the system of proof within the matters when the inquiry occurs in the short form, such system requires the conretization and individualization within the content of special Chapter of the criminal procedure code which regulates the above-mentioned legal Institution.